Conductivity mechanism probed by ion transmission through nanocapillaries during the discharging process. (July 2015) - Herczku, P; Juhász, Z; Kovács, S T S; Rácz, R; Biri, S; Sulik, B; Stolterfoht, N
Synopsis: We studied the decrease of the guided transmission due to discharging of nanocapillary walls in poly-ethylene-terephthalate (PET) foil. After developing the stable guided transmission, the ion beam was switched off and the transmission was tested time to time by short pulses. The transmission monotonically decreased but its time dependence significantly deviated from a simple exponential decay. Our results suggest a non-linear connection between the guiding field and the depleting current of the deposited charge.